The impact of social participation on the quality of life among older adults in China: a chain mediation analysis of loneliness, depression, and anxiety - Lu-Yin Liang (Frontiers in Public Health)
This cross-sectional study investigates the impact of social participation on the quality of life (QOL) among older adults in China. Using convenience sampling, data were collected from 508 individuals aged 60 and above (M_age = 70.53 ± 7.90 years; 56.5% women). Statistical analyses were conducted using SPSSAU software, including Pearson correlation analysis to assess relationships between social participation, psychological health indicators (loneliness, depression, and anxiety), and QOL. Multiple regression analysis and chain mediation analysis were subsequently performed to explore the mediating effects of loneliness, depression, and anxiety on the relationship between social participation and QOL. The results indicated significant correlations between social participation and loneliness (r = −0.313, p < 0.001), depression (r = −0.487, p < 0.001), anxiety (r = −0.305, p < 0.001), and QOL (r = 0.476, p < 0.001). The mediation analysis revealed significant chain mediation effects of loneliness, depression, and anxiety on the relationship between social participation and QOL (β = 0.006, p < 0.001, 95% CI [0.001, 0.007]). Higher levels of social participation were associated with lower levels of loneliness, which in turn reduced depression and anxiety, thereby enhancing QOL. These findings highlight the importance of promoting social participation to improve psychological wellbeing and QOL among older adults in China. The study advocates for active social engagement and the provision of relevant services, as well as psychological support and emotional counseling for those facing mental health challenges due to insufficient social participation.